The Concept of Agency, Animal Wellbeing, and the Practical Realities of Ex Situ Breeding Programs in Zoos and Aquariums - Max Norman; Sabrina Brando (Journal of Zoological and Botanical Gardens)
Conservation and animal wellbeing are two key goals of the modern zoo and aquarium. In the case of ex situ conservation breeding programs, there is a unique paradox between these concepts; on some occasions, facilities must balance and mitigate arising conflicts between the wellbeing of animals with the goals of the conservation project. Exerting control over the reproductive lives of animals—choosing when and where they breed, whom they breed with, whether breeding is prohibited altogether, and so on—results in an inherent reduction in the animal’s agency. Considering the growing recognition that providing choice and control to animals enhances wellbeing, it is essential to examine how populations and their breeding are managed. The present review presents challenges in supporting agency for animals bred ex situ by thoroughly exploring the practical realities of working with these animals. Various challenges and areas of consideration, including current research directions, suggestions for future practices, and opportunities moving forward, are highlighted. The importance of careful population management in maximising wellbeing, including the inherent dichotomy of the necessity to limit some reproductive autonomy to preserve animal wellbeing while meeting the needs of breeding programs.